Правові засади діяльності міських органів місцевого самоврядування Західної України в складі Польщі (1918-1939 рр.) - Юхимюк, Ольга Михайлівна; Yukhymyuk, O. (Львівський національний університет ім. І. Франка, 2004)
Міське самоврядування в Західній Україні (Східній Галичині і Західній Волині) після включення цих територій в склад Польщі було розрізненим, хоча компетенції міських органів самоврядування майже співпадала. Польський закон 1933 року об’єднав різні системи самоврядування, обмеживши компетенцію міських самоврядних установ. City self-government in Western Ukraine (in the East Galichina and Western Wolyn) after including of these territories in composition of Poland was separate, although to jurisdiction of city organs of self-government coincided almost. The Polish law of 1933 year united different systems of self-government, limiting jurisdiction of city self-governing establishments
Legal frameworks of activity of city organs of local self-government of Western Ukraine in Poland (1918-1939)
Keywords: Західна Україна; самоврядування; Western Ukraine; self-government